Pharmacoepidemiological studies: methodology and regulation - D. Yu. Belousov; A. E. Cheberda (Izdatelstvo OKI, 2018)
This article describes the methodology of pharmacoepidemiological studies that help to research the efficacy and safety of drugs in real clinical practice at the level of a population or large groups of patients, promoting the rational and economically acceptable use of the most effective and safe drugs.